Nitrogen balance of bullocks fed Cratylia argentea and Brachiaria arrecta Hay - Valles de la Mora, Braulio; Castillo-Gallegos, Epigmenio (Ecosistemas y Recursos Agropecuarios, 2018)
Four experimental diets or treatments formed with incremental proportions of the foliage of tropical shrub legume Cratylia argentea and decremental proportions of Tanner grass (Brachiaria arrecta) hay: T1, 0:100; T2, 15:85; T3, 30:70; and T4, 45:55 were evaluated using four Holstein-Zebu bullocks (214.5 9.3 kg) conned in individual pens, under a balanced 4 x 4 latin square design. The crude protein (CP, %) content of C. argentea was 19.3 ± 6%, and in the grass was 6.2 ± 3%. The intake of DM increased as the C. argentea level in the diet increased. Blood urea-N (BUN) showed a linear increase from T1 to T4, observing its highest concentration at feeding time and six-hours after in T4: 12.00 and 14.75 mg dL-1, respectively. Purine derivatives (uric acid and allantoin) were not affected by treatments (p > 0.05). The increase of the legume in the diet improved the DM intake and digestibility, and led to N-balance from negative in T1 and T2, to positive in T3 and T4. The legume proportion in a basal diet of the grass B. arrecta must be 30% at least.